Structural and functional alterations in the colonic microbiome of the rat in a model of stress induced irritable bowel syndrome. (2nd January 2017) - Fourie, Nicolaas H.; Wang, Dan; Abey, Sarah K.; Creekmore, Amy L.; Hong, Shuangsong; Martin, Christiana G.; Wiley, John W.; Henderson, Wendy A.
ABSTRACT: Stress is known to perturb the microbiome and exacerbate irritable bowel syndrome (IBS) associated symptoms. Characterizing structural and functional changes in the microbiome is necessary to understand how alterations affect the biomolecular environment of the gut in IBS. Repeated water avoidance (WA) stress was used to induce IBS-like symptoms in rats. The colon-mucosa associated microbiome was characterized in 13 stressed and control animals by 16S sequencing. In silico analysis of the functional domains of microbial communities was done by inferring metagenomic profiles from 16S data. Microbial communities and functional profiles were compared between conditions. WA animals exhibited higher α-diversity and moderate divergence in community structure (β-diversity) compared with controls. Specific clades and taxa were consistently and significantly modified in the WA animals. The WA microbiome was particularly enriched in Proteobacteria and depleted in several beneficial taxa. A decreased capacity in metabolic domains, including energy- and lipid-metabolism, and an increased capacity for fatty acid and sulfur metabolism was inferred for the WA microbiome. The stressed condition favored the proliferation of a greater diversity of microbes that appear to be functionally similar, resulting in a functionally poorer microbiome with implications for epithelial health. Taxa, with known beneficial effects, were found to be depleted, which supports their relevance as therapeutic agents to restore microbial health. Microbial sulfur metabolism may form a key component of visceral nerve sensitization pathways and is therefore of interest as a target metabolic domain in microbial ecological restoration.